2019
DOI: 10.1111/1462-2920.14769
|View full text |Cite
|
Sign up to set email alerts
|

Dual functions of AreA, a GATA transcription factor, on influencing ganoderic acid biosynthesis in Ganoderma lucidum

Abstract: Summary Nitrogen metabolism repression (NMR) has been well studied in filamentous fungi, but the molecular mechanism of its effects on fungal secondary metabolism has been generally unexplored. Ganoderic acid (GA) biosynthesis in Ganoderma lucidum differs between ammonia and nitrate nitrogen sources. To explain the functions of NMR in secondary metabolism, AreA, which is a core transcription factor of NMR, was characterized in G. lucidum. The transcription level of AreA was dramatically increased (approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Genetic transformation systems, including Agrobacterium tumefacien ‐mediated and polyethylene glycol (PEG)‐mediated transformations, have been developed in G. lucidum (Shi et al , ; Xu et al , ; Xu and Zhong, ) and have been successfully used to enhance the production of bioactive compounds, such as ganoderic acids and polysaccharides (Zhou et al , ; Li et al , ; Zhang et al , , ; Fei et al , ; Xu et al , ). Gene silencing systems have also been used for the partial suppression of genes of interest in G. lucidum (Mu et al , ; Liu et al , ; Zhu et al , ). So far, however, targeted gene deletion has not been established in Ganoderma , although it would be a powerful tool for G. lucidum research in the post‐genomic era.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic transformation systems, including Agrobacterium tumefacien ‐mediated and polyethylene glycol (PEG)‐mediated transformations, have been developed in G. lucidum (Shi et al , ; Xu et al , ; Xu and Zhong, ) and have been successfully used to enhance the production of bioactive compounds, such as ganoderic acids and polysaccharides (Zhou et al , ; Li et al , ; Zhang et al , , ; Fei et al , ; Xu et al , ). Gene silencing systems have also been used for the partial suppression of genes of interest in G. lucidum (Mu et al , ; Liu et al , ; Zhu et al , ). So far, however, targeted gene deletion has not been established in Ganoderma , although it would be a powerful tool for G. lucidum research in the post‐genomic era.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the decrease in GS activity was not due to the GS content. Based on the findings in our previous study, we wondered whether NO, which is an active gas that could burst in nitrate cultivation (Zhu et al ., 2019), affects GS activity via posttranslational regulation. We examined the effect of NO on GS activity in fermentation as our previous study has revealed that the addition of NO donor (SNP) or extruder (PTIO) could increase or decrease the intracellular NO content in the mycelia of G .…”
Section: Resultsmentioning
confidence: 99%
“…We examined the effect of NO on GS activity in fermentation as our previous study has revealed that the addition of NO donor (SNP) or extruder (PTIO) could increase or decrease the intracellular NO content in the mycelia of G . lucidum (Zhu et al ., 2019). SNP addition decreased GS activity by 28.5% under ammonia conditions, whereas PITO increased GS activity by 15.3% under nitrate conditions compared with the control (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations